Influence of end distances on the failure of composite bolted joints. (March 2015) - Zhang, Jianyu; Liu, Fengrui; Zhao, Libin; Zhi, Jie; Zhou, Longwei; Fei, Binjun
To explore the physical effect of end distances on mechanical behaviors of composite bolted joints, series of single-bolt composite joints designed with different end distances were tested. In conjunction with the experimental work, a numerical progressive damage method is introduced to trace the damage process from the onset and propagation up to ultimate failure of the joints. A group of material degradation factors is presented by a trial-and-error method to establish three-dimensional progressive damage models of the bolted joints. The progressive damage analyses show that the predicted load–displacement curves, failure loads, and failure patterns of bolted joints with different end distances are in good agreements with the related experimental outcomes. From the experimental and numerical results, it follows that the cleavage failure gradually switches to the bearing failure with the increasing ratio of E / D ranged from about 2 to 4. An economic and suitable ratio of E / D  ≈ 3 is provided for the bolted joints made of X850 carbon/epoxy composites with balanced and symmetric layups [45/0/−45/0/90/0/45/0/−45/0]s . The understanding of the effect of E / D on the mechanical behaviors including the strength, stiffness, and failure patterns of single-bolt joints is strengthened.